Characteristics of Students’ Intuitive Thinking in Solving Mathematical Problems - Ulpah, Maria (International Conference of Moslem Society, 2019)
Intuition is one of important thing in the process of solving mathematical problems. It works as cognitive mediation. In this understanding, intuition can be made as a bridge to students' understanding so that it can be accessed in linking imagined objects with the desired alternative solutions. In other words, students can determine what strategies or steps should be taken to get a problem solution, especially contextual problems that have completion steps that cannot be accessed directly. Intuitive thinking often occurs in mathematical problem solving. This was also seen in the mathematical students of IAIN Purwokerto. Based on the teaching experience so far, it was found that many students gave spontaneous answers without analyzing first. So, the researcher studied how characteristics of students’ intuitive thinking are. This research used qualitative with descriptive-exploratory type of research and used test to identify the characteristics of students’ intuitive thinking in solving mathematical problems. Results showed that students’ characteristics consisted of extrapolative, implicitly, persistently, coercively, and the power of synthesis.